An Expedient Synthesis of Ketocalix[6]arene Hexamethyl Ether - Itzhak, Norbert; Biali, Silvio E. (Synthesis, 2018)
p-tert-Butylcalix[6]arene hexamethyl ether was oxidized in one step to the corresponding ketocalix[6]arene via photochemical bromination (100 W spot lamp) with NBS in a chloroform/water mixture. A pentamethyl ketocalix[6]arene derivative was obtained by reaction of the ketocalix[6]arene hexamethyl ether with boron tribromide dimethyl sulfide complex, and characterized by X-ray crystallography. In the presence of base, the compound undergoes an intramolecular nucleophilic aromatic substitution reaction.
Keywords: calixarenes; bromine; cleavage; ether; oxidation; phenols